Key issues in education and social justice - Smith, Emma (Education studies, key issues, 2018)
'This excellent book considers the extent to which policy and practice, particularly in the UK, have led to a more equitable education system and ultimately to a fairer society. The ideas and arguments are extremely accessible, wide-ranging and well-informed. A welcome addition to the reading list and one that I can highly recommend' - Jane Bates, Programme Leader fo Education Studies, Manchester Metropolitan University Inequalities can be experienced in different forms, from birth to school experiences to the many different modes of learning as we grow up.